Behavior and design of functionally graded concrete subject to triple impacts of the shaped charge, projectile penetration and explosion - Yin, Xuexiang; Lai, Jianzhong; Du, Longyu; Zhou, Jiehang; Kang, Ningyu (Composite structures, 2024)
The present issue is how to improve the concrete structure to resist multiple impacts of the tandem warhead. This study developed an approach to design a functionally graded concrete (FGC) structure with fiber-graded (FG) and centralized high-strength aggregates (CHSA) to address this issue. The enhancement of the FG and CHSA in the concrete structure was verified by static mechanical performance tests and dynamic compressive simulation. The behavior of the FGC structure subject to the tandem warhead was investigated by the experimental and numerical dynamic destructive tests, including three stages: shaped charge, projectile penetration and explosion. There are three types of targets, including ultra-high-performance concrete (UHPC), ceramic aggregate reinforced (CAR) FGC and steel aggregate reinforced (SAR) FGC. The results showed that the SAR-FGC had the best multiple-impact resistance in concrete structures. The blocking effect to impact waves was improved by increasing the wave impedance of the anti-penetration layer. Energy absorption was increased by 7 times through the combined action of functional structures to ameliorate damage distribution. The triple destruction depth of it was reduced by 36% compared to UHPC. According to the Forrestal empirical equation, a penetration depth model was proposed for the FGC with jet damage.